2020
DOI: 10.1155/2020/2867505
|View full text |Cite
|
Sign up to set email alerts
|

A New Risk Polymorphism rs10403848 of CARD8 Significantly Associated with Psoriasis Vulgaris in Northeastern China

Abstract: Caspase recruitment domain family member 8 (CARD8) is an adaptor molecule that negatively regulates nuclear factor-κB (NF-κB) activation, interleukin (IL)-1β secretion, and apoptosis. These play important roles in the pathogenesis of psoriasis. Genetic variants of CARD8 have been associated with an increased risk of several inflammatory diseases and psoriasis in Europe. However, nothing is known about the association of the polymorphisms of CARD8 and psoriasis vulgaris (PsV) in the Han population of northeaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Currently, there are also many other studies on CARD8 polymorphisms for their activity under different conditions. For example, the CARD8 rs2043211 polymorphism was shown to protect against noise-induced hearing loss; 61 the CARD8 rs2043211 polymorphism may be associated with gout; 37 the CARD8 rs10403848 polymorphism was significantly associated with psoriasis vulgaris, 62 as the CARD8 rs7248320 polymorphism influenced KD susceptibility in our study. More SNP genes of CARD8 associated with KD susceptibility, treatment, prognosis, and outcome need to be clarified in the future.…”
Section: Discussionmentioning
confidence: 53%
“…Currently, there are also many other studies on CARD8 polymorphisms for their activity under different conditions. For example, the CARD8 rs2043211 polymorphism was shown to protect against noise-induced hearing loss; 61 the CARD8 rs2043211 polymorphism may be associated with gout; 37 the CARD8 rs10403848 polymorphism was significantly associated with psoriasis vulgaris, 62 as the CARD8 rs7248320 polymorphism influenced KD susceptibility in our study. More SNP genes of CARD8 associated with KD susceptibility, treatment, prognosis, and outcome need to be clarified in the future.…”
Section: Discussionmentioning
confidence: 53%
“…SNPs have been involved in a variety of diseases including PsV [ 1 , 7 , 8 ]. In this study, we investigated 18 polymorphisms reported in previous studies to be associated with metabolic syndrome and examined them in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic inflammatory disease caused by various factors including genetic factors, with psoriasis vulgaris (PsV) representing the most common type [ 1 ]. Recently, it is reported that psoriasis is related to metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The CARD8 gene, which is located on chromosome 19 (19q13.33), contains 22 exons, and rs10403848 is located in the last intron. A recent study reported that this newly discovered CARD8 polymorphism is significantly associated with psoriasis vulgaris, an immunologically mediated chronic inflammatory disease, in the Han population of northeastern China (27). Polymorphism rs2043211, which is a nonsense mutation resulting in a truncated CARD8 protein, is located in exon 5.…”
Section: Discussionmentioning
confidence: 99%